Empowerment Education Programmed for Teenagers as Health Cadres On Reproductive Health Awareness in Bojonegoro, Indonesia - Aris Handayani (Frontiers in Community Service and Empowerment, 2023)
Puberty makes adolescents aware of their potential and become more expressive in exploring their sexual organs and behaviour. The increasing number of adolescent reproductive health issues, especially those related to personal hygiene, the provision of information, services and health education to adolescents is very important. The solution to the problem of lack of knowledge about the function of reproductive organs is done by increasing counselling on the introduction of the reproductive system, female personal hygiene, male personal hygiene, unwanted pregnancy and understanding STIs & HIV/AIDS by using the concepts of input, process, outcome and impact. The method used in community empowerment activities is in the form of counselling activities for adolescent health cadres at Al Munawar Islamic Boarding School as many as 30 students. The purpose of this community service is to increase the knowledge and skills of adolescent cadres through training and the formation of adolescent cadres aware of reproductive health at Pondok Pesantran Al Munawar Kunci Village, Dander Kab. Bojonegoro. After the provision of Health Education, the results of activities in the form of Increased knowledge obtained Pre test and Post test scores obtained. The average value of the Pre Test is 51.75 and the average Post test is 82.88, there is an increase in knowledge of 31.13% trainees, on Skills in Counseling or IEC on Adolescent Reproductive Health obtained The average value of IEC is 84.38 and the results are 66.7% very good results. The implication of this research is the active role of adolescents and the community in increasing Adolescent Health Knowledge about reproductive health so as to produce a healthy young generation in preparing their reproduction